2016
DOI: 10.18689/mjd-1000103
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analyses of Urine Exosomes reveal New Biomarkers of Diabetes in Pregnancy

Abstract: Objective To evaluate 24 hour urine exosome protein content changes among pregnant US subjects with diabetes and obesity during early pregnancy. Methods The exosome proteome content from 24 hour urine samples of pregnant subjects with gestational diabetes mellitus (GDM, N=8) and pre-gestational Type 2 diabetes (PGD, N = 10) were compared with control samples (CTRL, N = 10) obtained at week 20 of pregnancy. Differences in exosome protein load between groups was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Pathway analysis revealed that many of these proteins are involved in energy production and inflammation [104]. Analysis of urinary exosomes revealed that the damage associated molecular pattern (DAMP) protein S100A9 was present at higher levels in exosomes in GDM and could be used as valid biomarker of inflammatory processes and immune responses [105]. In addition, increased levels of miRNA members of the C19MC region were found in exosomes during GDM: miR-518a-5p, miR-518b, miR-518c, miR-518e, miR-520c-3p, and miR-525-5p [106,107].…”
Section: Gestational Diabetes Mellitus (Gdm)mentioning
confidence: 99%
“…Pathway analysis revealed that many of these proteins are involved in energy production and inflammation [104]. Analysis of urinary exosomes revealed that the damage associated molecular pattern (DAMP) protein S100A9 was present at higher levels in exosomes in GDM and could be used as valid biomarker of inflammatory processes and immune responses [105]. In addition, increased levels of miRNA members of the C19MC region were found in exosomes during GDM: miR-518a-5p, miR-518b, miR-518c, miR-518e, miR-520c-3p, and miR-525-5p [106,107].…”
Section: Gestational Diabetes Mellitus (Gdm)mentioning
confidence: 99%
“…Bioinformatic analysis showed that the exosomal proteins in GDM target pathways were mainly associated with energy production, inflammation, and metabolism ( 113 ). In addition, the EVs proteome content from urine samples of pregnant patients with GDM was compared with that of controls, identifying 646 and 734 proteins in EVs from urine samples of controls and GDM patients, respectively ( 114 ). Notably, S100 calcium binding protein A9, a damage-associated molecular pattern signal, was found to be significantly increased in GDM ( 114 ), providing insights into maternal changes during diabetic pregnancy.…”
Section: Role Of Non-coding Rnas and Evs In Gdmmentioning
confidence: 99%
“…In addition, the EVs proteome content from urine samples of pregnant patients with GDM was compared with that of controls, identifying 646 and 734 proteins in EVs from urine samples of controls and GDM patients, respectively ( 114 ). Notably, S100 calcium binding protein A9, a damage-associated molecular pattern signal, was found to be significantly increased in GDM ( 114 ), providing insights into maternal changes during diabetic pregnancy. Further research to explore the role of types of proteins in EVs and clinical tests to confirm their importance are needed in the future.…”
Section: Role Of Non-coding Rnas and Evs In Gdmmentioning
confidence: 99%
“…The concentration of circulating exosomes is found to be elevated in GDM cases [ 48 ]. Since circulating exosomes could be originated from the placenta and deliver to various types of cells, it is a novel and promising approach to elucidate the physiological mechanisms of GDM based on the proteins identified in the isolated plasma exosomes [ 41 ] or even urine exosomes [ 45 ]. It is generally accepted that the basic pathogenesis of GDM is insulin resistance.…”
Section: Summary Of Proteomic Studies Of Gdmmentioning
confidence: 99%
“…First, peripheral blood and urine samples were drawn before diagnosis and used to identify biomarkers for early prediction [ 27 , 32 , 37 , 38 , 42 , 47 ]. Second, peripheral blood and urine exosome samples were also drawn at the same time with diagnosis and used to identify biomarkers for precision diagnosis or classification [ 29 , 31 , 41 , 45 ]. Third, placental tissues, umbilical blood, omental adipose tissues, abdominus skeletal muscle tissue, and colostrum whey were obtained during or after delivery and used to identify markers for the pathogenesis of GDM or fetal outcomes [ 28 , 30 , 33 36 , 39 , 40 , 43 , 44 , 46 ].…”
Section: Summary Of Proteomic Studies Of Gdmmentioning
confidence: 99%